Human agro-energy optimization for business and industry - Vasant, Pandian; Rodriguez-Aguilar, Roman; Litvinchev, I. S.; Marmolejo Saucedo, Jose Antonio (IGI Global, 2023)
The edited book on humanized optimization approaches for Smart Energy and Agro-Business Industry is a critical scholarly resource that examines efficient use of modern smart farming and renewable energy sources which have a positive impact on sustainable development. Featuring coverage on cogeneration thermal modules, photovoltaic (pv) solar, and renewable energy systems (RES) application practices, this publication is geared towards academics, advocates, government officials, policy makers, humanized managers, practitioners, professionals, and graduates interested in the latest research on smart human energy and smart optimization for sustainable rural development